Emerging Role for Corticotropin Releasing Factor Signaling in the Bed Nucleus of the Stria Terminalis at the Intersection of Stress and Reward - Silberman, Yuval; Winder, Danny G. (Frontiers in Psychiatry, 2013)
Stress and anxiety play an important role in the development and maintanence of drug and alcohol addiction. The bed nucleus of the stria terminalis (BNST), a brain region involved in the production of long-term stress related behaviors, plays an important role in animal models of relapse, such as reinstatement to previously extinguished drug-seeking behaviors. While a number of neurotransmitter systems have been suggested to play a role in these behaviors, recent evidence points to the neuropeptide corticotropin releasing factor (CRF) as being critically important in BNST mediated reinstatement behaviors. The BNST is a complex brain region with multiple afferent and efferent systems and a variety of cell types and there has only been limited work trying to understand how CRF modulates this complex neuronal system. Recent work from our lab and others have begun to unravel these BNST neurocircuits and explore their roles in CRF-related reinstatement behaviors. This review will examine the role of BNST CRF signaling in drug addiction and reinstatment with an emphasis on critical neurocircuitry within the BNST that may offer new insights into treatments for addiction.